Aleitamento materno exclusivo: conhecimento das puérperas em puerpério imediato em um hospital público na Transamazônica - PEREIRA, Carlos Wagner Machado (2022)
One of the most important actions in the creation of bonds between mother and baby from birth is Exclusive Breastfeeding (EB). The current recommendation is that the child is breastfed within the first hour of life and for up to two years or more and in the first six months, that she receives only breast milk. OBJECTIVE: Evaluate the knowledge about EB of postpartum women in their immediate postpartum period regarding the importance, benefits of EB and the weaning period; know the social profile of the participants; identify the main difficulties in breastfeeding in the immediate postpartum period. METHODOLOGY: The work adopted a descriptive, cross-sectional study with a quantitative-qualitative approach with a sample of 70 postpartum women admitted to rooming-in (ALCON) at the Hospital Geral de Altamira São Rafael. Inclusion criteria were puerperal women hospitalized in EBF, aged 18 years and over, performed vaginally or by cesarean, received during the study period and who remained hospitalized with the NBs for at least 24 hours and excluded; patients in labor or in obstetric evaluation in the prepartum, as well as those who were not accepted during the research period, age under 18, indigenous mothers. Data from each patient were collected in a standardized form and later evaluated. RESULTS: 88% of the participants are among the age groups up to 31 years old, 57% had six or more prenatal consultations, 76% did not receive training on EBF during their prenatal consultations. 63% stated that they breastfed all their children, despite the fact that around 27% of the population surveyed were their first pregnancy. 80% said that breast milk is the food that has all the nutrients that the baby needs until the age of six months, 29% say that breast milk has a greater amount of benefits than cow's milk. As for weaning, the highest rates were 1 year and 2 years, 36% and 30%, respectively. 26% of nursing mothers indicated that they feel tired while breastfeeding and 40% have difficulties in the act of breastfeeding, the main ones being: related to milk (little milk, weak milk), psychological (baby crying and stress), orientation (position of breastfeeding and baby latching), physiological (mastitis) and temporal (dawn). CONCLUSION: Most participants went to six prenatal consultations; however, they claim not to receive training on EBF. They reported breastfeeding for at least six months, however, if the baby did not want to take the breast, they would no longer offer it. It is found that there is weak knowledge about the function and benefits of breast milk. There are no problems when it is time to breastfeed, nor do they feel tired, however they have difficulties in getting the baby to the breast. Therefore, a multidisciplinary work of health education in the field of breastfeeding for pregnant women in the Transamazônica and Xingu region is important, focused on the weaknesses detected in the study and these are notified to become shared information so that future mothers assisted in reference hospitals feel more confident about breastfeeding in your immediate postpartum period.